(untitled) (di/segni, 2017)
This work aims to develop new readings of the poetics and the politics of Angela Carter’s The Bloody Chamber and Other Stories (1979) in the light of the bodily metamorphoses represented in the fairy tales. Metamorphic processes can be said to inform the stories of the collection both in a thematic and a stylistic perspective and address the need to rethink human experience altogether, especially as regards heterosexual relationships and power distribution between the sexes. By exhibiting the body and its changes in texts where it is traditionally concealed or treated as a natural essence, Carter foregrounds the powerful potential of metamorphosis – as a concept, a topic, a structuring and guiding principle, and as a proposed model – in order to expose and challenge patriarchal myths and discourses, which slow down or even prevent the progressive empowerment of women’s conditions and positions within society (in the Seventies as well as today). Carter’s creativity and commitment are engaged in a productive dialogue with some contemporary feminist philosophers, to show how and why her fairy tales and their transformative potential can be – once again – signified anew.